ReviewInc : success from segmentation - Palmer, Lynda; Rapier, Stephen M.; Shanahan, Doreen E. ([London] : SAGE, 2016)
As online reviews began to impact the customer buying process, National Positions, a worldwide leader in internet marketing services based in Agoura Hills, California, launched a software offering called Positive Reviews (September 2011). Using proprietary technology, this software as a service (SaaS) provided a cost-effective solution to help clients manage their reputations through online reviews. In July 2012, National Positions formed a separate entity, ReviewInc, to focus on the sales and further enhancement of the offering. While the company had secured several early customers, they were spread over a range of verticals including food service, automotive, medical, travel, leisure, property management and legal services. Management realized that successful commercialization required them to focus. This case study examines this topic.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Internet marketing -- Case studies